Odpowiedzi

Najlepsza Odpowiedź!
2010-03-30T14:22:27+02:00
A) 2x-1+4x-2+x+1=7x-2
b) 2x-2+2x+1+3x-1=7x-2
c) 3x+1+x-1+3x-2=7x-2
d) 2x-1+2x-2+3x+1=7x-2
e) 4x-2+2x+1+x-1=7x-2
f) x+1+3x-1+3x-2=7x-2
g) 2x-1+2x+1+3x-2=7x--2
h) x+1+2x+1+3x+1=6x+3

=]]
momisia
1 5 1
2010-03-30T14:24:20+02:00
A) 2x-1+4x-2+x+1=7x-2
b) 2x-2+2x+1+3x-1=7x-2
c) 3x+1+x-1+3x-2=7x-2
d) 2x-1+2x-2+3x+1=7x-2
e) 4x-2+2x+1+x-1=7x-2
f) x+1+3x-1+3x-2=7x-2
g) 2x-1+2x+1+3x-2=7x-2
h) x+1+2x+1+3x+1=6x+3

2010-03-30T14:25:47+02:00
A)7x-2
b)7x-2
c)7x-2
d)7x-2
e)7x-2
f)7x-2
g)7x-2
h)6x+3
czekam na naj